1997
DOI: 10.1021/om961012p
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, Spectroscopy, and Reactivity of a Metallabenzene1

Abstract: A rare example of a stable metallabenzene complex has been synthesized in three high-yield steps from (Cl)Ir(PEt3)3. In the first step, (Cl)Ir(PEt3)3 is treated with potassium 2,4-dimethylpentadienide to produce the metallacyclohexadiene complex mer-CHC(Me)CHC(Me)CH2Ir(PEt3)3(H) (1b) via metal-centered CH bond activation. Treatment of 1b with methyl trifluoromethanesulfonate removes the hydride ligand, producing [CHC(Me)CHC(Me)CH2Ir(PEt3)3]+O3SCF3 - (2). Finally, deprotonation of 2 with base yields the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
157
1
13

Year Published

1998
1998
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(181 citation statements)
references
References 34 publications
8
157
1
13
Order By: Relevance
“…[22] In 1989, Bleeke et al reported the synthesis of the first stable iridabenzene 4 utilizing 2,4-dimethylpentadienide as a source for the carbon backbone. [17,29] Using the resultant iridabenzene as a starting point, the Bleeke group extensively examined the chemistry of such complexes. [17] When exposed to EAS conditions, it was found that the electrophiles react preferentially with the electron-rich metal center.…”
Section: Historical Perspectivesmentioning
confidence: 99%
See 4 more Smart Citations
“…[22] In 1989, Bleeke et al reported the synthesis of the first stable iridabenzene 4 utilizing 2,4-dimethylpentadienide as a source for the carbon backbone. [17,29] Using the resultant iridabenzene as a starting point, the Bleeke group extensively examined the chemistry of such complexes. [17] When exposed to EAS conditions, it was found that the electrophiles react preferentially with the electron-rich metal center.…”
Section: Historical Perspectivesmentioning
confidence: 99%
“…[17,29] Using the resultant iridabenzene as a starting point, the Bleeke group extensively examined the chemistry of such complexes. [17] When exposed to EAS conditions, it was found that the electrophiles react preferentially with the electron-rich metal center. Additionally, it was found that when exposed to dienophiles, these iridabenzenes behave more like cyclohexatrienes and undergo cycloaddition reactions.…”
Section: Historical Perspectivesmentioning
confidence: 99%
See 3 more Smart Citations